2001
DOI: 10.1177/10454411010120060401
|View full text |Cite
|
Sign up to set email alerts
|

Adhesive Mechanisms Regulating Invasion and Metastasis in Oral Cancer

Abstract: It is the relentless invasion and growth into surrounding tissue that characterize oral squamous cell carcinoma. Metastasis is perhaps the most challenging and important aspect of cancer progression, in that it generally signifies limited survival and ineffective therapy. Inherent in metastasis is invasion, the process by which cells infiltrate into adjacent tissues, degrading basement membranes and extracellular matrix and disrupting tissue architecture and sometimes organ function. The factors that regulate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
53
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 141 publications
1
53
0
2
Order By: Relevance
“…E-cadherin is the major cadherin expressed on the surface of normal epithelial cells (37). E-cadherin expression is reduced during tumor progression and metastasis, and associated with poor prognosis in a variety of cancers (38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…E-cadherin is the major cadherin expressed on the surface of normal epithelial cells (37). E-cadherin expression is reduced during tumor progression and metastasis, and associated with poor prognosis in a variety of cancers (38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previous studies reported that an alteration in the expression of adhesion-related molecules was associated with a poor prognosis in OSCC patients [5][6][7][8]. In addition, several tissue and biological markers have been identified as possible indicators of the tumor aggressiveness and metastatic capability of tumors 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been reported that an alteration in the expression of adhesion-related molecules is associated with poor prognosis in OSCC patients [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%